Follow-up investigation revealed that sheep may play an important role in the transmission of Leptospira spp. infection in Caatinga biome field conditions - de Araujo Santos, Julio Cesar; de Vasconcelos, Igor Felipe Ferreira; Nogueira, Denise Batista; Júnior, João Pessoa Araújo [UNESP]; Malossi, Camila Dantas [UNESP]; Santos, Carolina de Sousa Américo Batista; Alves, Clebert José; Silva, Maria Luana Cristiny Rodrigues; de Azevedo, Sérgio Santos (Elsevier, 2024)
Leptospira spp. is poorly studied in sheep raised in field Caatinga biome conditions. We conducted a follow-up investigation for Leptospira spp. infection in sheep reared in field conditions in the Caatinga biome. Serum, urine and vaginal fluid samples were collected from adult sheep over five collection periods in rainy and dry seasons. Serological diagnosis was performed using the microscopic agglutination technique (MAT) and polymerase chain reaction (PCR) was applied to urine and vaginal fluid samples. Overall, 45 sheep were monitored during the five collections: July 15, September 30 and November 27 of 2020 and March 3 and June 25 of 2021. The frequencies of seropositive animals at MAT (cut-off 25) per collection were 13.3 %, 15.6 %, 31.1 %, 20 % and 35.6 %, respectively. The most frequent serogroups in all collections were Autumnalis, Ballum, Icterohaemorrhagiae and Pyrogenes. PCR of urine and vaginal fluid carried out for the first two collections detected an average of 28.1 % and 48.1 % positive animals, respectively. In the other three collections, there was no PCR positivity for either urine or vaginal fluid. Two samples of vaginal fluid from the first collection were sequenced and showed 99 % similarity to L. interrogans and L. santarosai. The occurrence of Leptospira spp. genital carrier sheep may be important in the spread of infection in the Caatinga biome field conditions, where the environment is often unfavourable and challenges the adaptability of Leptospira spp., forcing the agent to seek alternative routes of transmission and highlighting the public health exposure risk, mainly in people who are at occupational risk.
Keywords: Caatinga biome; Epidemiology; Field conditions; Follow-up investigation; Leptospirosis; Small ruminant